Opportunities for improvement of graphical education in distance learning using learning game - Jurāne, Ieva; Znotiņa, Inta; Mackus, Austris; Snipkis, Andris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Novaday's situation in the graphical education is the same all over the world. Small number of contact hours and very different entrance level of the first year students at tertiary institutions. To improve the situation the computer game for the training of the basic skills in technical drawing is created and verified. 120 first year students of civil engineering speciality were involved and 50 of them played the game at home on an optional basis, but other students did not. All the students completed the graphical test after three weeks and results were compared. The number of mistakes was higher for the students who did not play the game. The average mark was higher for the students who played the game. The results of the experiment showed positive influence on learning results and attitude. The paper is recommended to the persons who work in the field of graphical education and create the technical educational aids for this aim. Paper is recommended for all interested people as well.